Game theory analysis in Indonesia’s shipping industry: Case study agreement between PT. X and PT. Y - Heru Susanto (Scientific Journal of Gdynia Maritime University, 2020)
Nowadays, the container shipping industry in Indonesia has a tendency to oligopoly, even in one shipping route. Two big shipping liners in Indonesia, PT. X and PT. Y, have been dominating sales on the Surabaya-Banjarmasin route. The aim of this study is to know how the liners behave in an oligopoly, making decisions that are profitable for both parties. The agreement on challenge, competition, and cooperation between PT. X and PT. Y in serving shipping services is the main focus in this study. The methodology used is a game theory approach to show the possible strategies in rates and supply competition. The result shows that the agreement between PT. X and PT. Y consisted of price decision and supply quantity. The price decision is rated at a lower price of USD 300/TEU where P = MC which has no incentive. While the agreement on supply quantity is 26.000 TEUs in total. Moreover, the cooperative agreement between the shipping liners is a joint allience which not depend on each capacity ratio.